Intrusion Detection System Using Hybrid Classification Technique - Wankhede, Rajesh; Chole, Vikrant (International Journal of Computer Sciences and Engineering, 2025)
Cyber Security is one of the key elements of any system. Breaching of cyber security can lead to loss of confidential and private data. To prevent the attacks on network an Intrusion Detection System Using Hybrid Classification Technique is proposed. This IDS uses a decision tree algorithm to classify the known attack types in the dataset and SVM is used to classify the normal data from the dataset, there by detecting the unknown attacks. Dataset used is the NSL-KDD Dataset.